An overview of methods and instruments for the assessment of occupational exposure to nanoparticles - Vahideh Abolhasannejad; Mohammad Javad Assari (Muhandisī-i bihdāsht-i ḥirfah/ī, 2015)
Background & objective:: In recent years, there has been a dramatic increase in the application of nanotechnology in industries and the number of workers occupied in different processes of research on and construction, production and residue disposal of products containing nanoparticles. Despite this growth, however, there is still a dearth of information on the risk of occupational exposure to these materials. Due to the growing application of nanoparticles in the workplace, selecting suitable sampling and characterization techniques and instruments as well as investigating their efficiency for the evaluation of occupational exposure is very important.